2006
DOI: 10.1002/cne.21068
|View full text |Cite
|
Sign up to set email alerts
|

Medullary dorsal horn neurons providing axons to both the parabrachial nucleus and thalamus

Abstract: It has often been suggested that the trigemino- and spino-thalamic pathways are highly implicated in sensory-discriminative aspects of pain, whereas the trigemino- and spino-parabrachial pathways are strongly implicated in affective/emotional aspects of pain. On the other hand, the superficial laminae of the spinal dorsal horn, where many nociceptive neurons are distributed, have been reported to contain projection neurons innervating both the parabrachial nucleus (PBN) and thalamus by way of axon collaterals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 79 publications
6
23
0
Order By: Relevance
“…However, the present study clearly demonstrates that the thalamocortical thermosensory transmission is not required for eliciting heat- or cold-avoidance behaviour, while the LPB is a brain site that plays an essential role in the central circuit for these thermoregulatory behaviours. The LPB receives numerous projections from the dorsal horn 1820 , which include axonal collaterals from spinothalamic and trigeminothalamic projections 21, 22 . The LPB contains two separate populations of neurons responsive to either cutaneous warm- or cool-sensory input; they are activated by exposure of animals to warm or cool ambient temperature or by direct warming or cooling of the trunk skin with a water jacket 11, 12, 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study clearly demonstrates that the thalamocortical thermosensory transmission is not required for eliciting heat- or cold-avoidance behaviour, while the LPB is a brain site that plays an essential role in the central circuit for these thermoregulatory behaviours. The LPB receives numerous projections from the dorsal horn 1820 , which include axonal collaterals from spinothalamic and trigeminothalamic projections 21, 22 . The LPB contains two separate populations of neurons responsive to either cutaneous warm- or cool-sensory input; they are activated by exposure of animals to warm or cool ambient temperature or by direct warming or cooling of the trunk skin with a water jacket 11, 12, 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The LPB is a sensory mediating region that receives massive projections from the dorsal horn (8,25,36). These projections to the LPB include axon collaterals from thalamic projecting neurons in the spinal and trigeminal dorsal horns (57,75). An anatomical study revealed that axonal swellings from dorsal horn neurons are closely associated with postsynaptic structures of LPB neurons that project to the POA (105), supporting the view that the activation of POA-projecting LPB neurons in response to skin thermal challenges is caused by direct cutaneous thermosensory inputs from dorsal horn neurons (Fig.…”
Section: Cutaneous Thermosensory Afferent Pathways To the Poamentioning
confidence: 99%
“…The TRP channels in the thermoreceptor central endings may also provide a substrate for spinal cord or trigeminal nucleus temperature to influence the level of thermal effector activity. In turn, spinal and trigeminal lamina I neurons collateralize and innervate the thalamus, providing the neural substrate for cutaneous thermosensory perception and localization (Craig et al, 1994; Craig, 2002), and the pontine lateral parabrachial nucleus (LPB) (Hylden et al, 1989; Li et al, 2006) (Fig. 1), responsible for triggering involuntary (e.g., autonomic, shivering and respiratory) thermoregulatory responses.…”
Section: Afferents Influencing Thermoeffector Activitymentioning
confidence: 99%